1997
DOI: 10.1098/rspb.1997.0026
|View full text |Cite
|
Sign up to set email alerts
|

Enigmatic phylogeny of skuas (Aves: Stercorariidae)

Abstract: SUMMARYMultiple sources of evidence show that the skuas (Aves : Stercorariidae) are a monophyletic group, closely related to gulls (Laridae). On morphological and behavioural evidence the Stercorariidae are divided into two widely divergent genera, atharacta and Stercorarius, consistent with observed levels of nuclear and mitochondrial gene divergence. atharacta skuas are large-bodied and with one exception breed in the Southern Hemisphere. Stercorarius skuas (otherwise known as jaegers) are smaller bodied and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
98
0
7

Year Published

2000
2000
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(109 citation statements)
references
References 45 publications
4
98
0
7
Order By: Relevance
“…Although the three small species of the northern hemisphere (Stercorarius spp.) are similar to each other and clearly differentiated from the Great Skua (Catharacta skua) of the northern hemisphere and all taxa breeding at the southern hemisphere, a mitochondrial DNA phylogeny revealed a closer relatedness of the Great Skua to one of the small northern skuas, the Pomarine Skua (S. pomarinus), than to any of the southern taxa (Blechschmidt et al, 1993;Cohen et al, 1997). The southern taxa formed a monophyletic clade with very short and shallow branches implying a recent and rapid colonization of the southern hemisphere.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the three small species of the northern hemisphere (Stercorarius spp.) are similar to each other and clearly differentiated from the Great Skua (Catharacta skua) of the northern hemisphere and all taxa breeding at the southern hemisphere, a mitochondrial DNA phylogeny revealed a closer relatedness of the Great Skua to one of the small northern skuas, the Pomarine Skua (S. pomarinus), than to any of the southern taxa (Blechschmidt et al, 1993;Cohen et al, 1997). The southern taxa formed a monophyletic clade with very short and shallow branches implying a recent and rapid colonization of the southern hemisphere.…”
Section: Introductionmentioning
confidence: 99%
“…Despite considerable research effort, the phylogenetic history of skuas remains enigmatic (Andersson, 1973;Blechschmidt et al, 1993;Cohen et al, 1997;Andersson, 1999a;Andersson, 1999b). Although the three small species of the northern hemisphere (Stercorarius spp.)…”
Section: Introductionmentioning
confidence: 99%
“…Louse collections resulting from a study on the phylogeny of skuas (Cohen et al 1997: 186) have shown that one species of Saemundssonia parasitises Stercorarius pomarinus (Temminck, 1815) and all species of Catharacta. Although Cohen et al (1997) applied the name Saemundssonia stresemanni Timmermann, 1949 to that species -originally described from specimens Z99044 Received 24 August 1999;accepted 29 October 1999 collected on Catharacta skua Briinnich, 1764 -the earliest available name for those lice is Saemundssonia euryrhyncha (Giebel, 1874) with Stercorarius pomarinus as type host. Timmermann (1957: 47) also recognised a single species of Saemundssonia parasitising both St. pomarinus and C. skua and referred to it as S. stresemanni.…”
Section: Introductionmentioning
confidence: 99%
“…The taxonomic nomenclature of the hosts follows Cohen et al (1997). In the synonymies, quotation marks (" ") are used for those binomial combinations which I regard as having been incorrectly applied by the author cited immediately after the closing quotation mark.…”
Section: Introductionmentioning
confidence: 99%
“…Skuas are large, gull-like polar birds belonging to the Stercorariidae (Cohen et al, 1997). The brown skua (Catharacta antarctica lonnbergi) is an Antarctic species and has a circumpolar distribution, while the South Polar skua (C. maccormicki) which breeds mainly on the Antarctic continent may be found north of the equator in winter.…”
mentioning
confidence: 99%